Sales Force Management Analysis: Sales Capability and ICT Development to Support PT. Holcim Indonesia Market Strategy - Marnaek, Sopar Matoga; Ibarat, Iriawan Alex (The Indonesian Journal of Business Administration, 2015)
Abstract – Holcim Indonesia then setting up milestone to grab as much as profit from growing Indonesian market and strengthened its footprint to prepare upcoming fiercer competition as predicted by analyst. One of biggest initiatives Holcim roll out to support sales force management strategy execution is Sales Force Dot Com (SFDC) which is Internet and Communication Technology (ICT) interface for the sales force to obtain real-time data and processing those data into real-time information that can be accessed by designated stakeholders using computer unit or mobile application. To optimize this expensive technology, the sales force required to be developed into an effective sales force, not only able to gather the data and conduct sales but also read the data and do the analysis on issues based on information and take action using problem solving methods and techniques. The writing particularly address how Holcim Indonesia could cope the gap between strategy and the operational capability in commercial directorate to gain maximum impact to the financial and market performance. This project research conducted by identified organization capabilities in operating capability, management infrastructure and field assessment. The author analyze the result and identified existed gap based on employees’ perspective. From the data, author concluded and identified actual problem and compare the result to initial hypothesis. At the end author will provide a recommendation to improve rate of success of commercial strategy execution. The company can use this writing as a reference and use the findings as comparison of improvement analysis conduct by the management. Keywords: sales force management, marketing and sales strategy, strategic execution, sales force dot com